Analysis of pediatric fixation equipment with audio-video for chest radiography examinations - Apriantoro, Nursama Heru; Supriyono, Puji; Prasetio, Heru; Sinaga, Citra Elisabet (SINERGI, 2024)
Pediatric patients are generally uncooperative during radiology examinations. Radiographic images can become blurry due to movement. This will cause to repeat examinations, thereby significantly increasing radiation exposure, and it can pose significant risks to children, patient families, and radiation workers. The research aims to create and test the effectiveness of a fixation device equipped with Audio-Visual elements for pediatric chest radiography examinations in Anteroposterior and Lateral projections. The experimental method involves developing the fixation device in the Radiodiagnostic Department Laboratory of Poltekkes Kemenkes Jakarta II. The effectiveness of the fixation device is assessed through surveys and interviews involving 66 respondents at hospitals in Jakarta from January to July 2023 during pediatric chest examinations. The average results indicate that the device can be used in hospitals (3.27±0.63), it’s safe to use (3.00±0.74), and highly effective (3.17±0.67). The overall average value of 3.16±0.68, suggests that the fixation device is suitable for use in pediatric chest examinations. The obtained images from the Anteroposterior and Lateral projections optimally describe of lung organs, the heart, and blood vessels within the thoracic cavity. Suggestions for further development of the safe device include the addition of leg supports, pediatric chair can be moved forward/backward and patient restraints to prevent falling or movement